PENGARUH PEMBERIAN PUDING NANAS REBUSAN DAUN SIRSAK TERHADAP PENURUNAN KADAR ASAM URAT PADA PASIEN HIPERURISEMIA DI PUSKESMAS SOSIAL - Jihan Sekar Ayu; Hana Yuniarti; Sriwiyanti Sriwiyanti; Eliza Eliza; Terati Terati (JURNAL MEDIA KESEHATAN, 2022)
Problems : Hyperuricemia caused because of an increasing uric acid in the blood which exceeds the normal limit, which is more than 7.0 mg/dl in men and 6.0 mg/dl in women. The prevalence of hyperuricemia in Indonesia is 7.3%, in South Sumatra it is 6.48%. One of the non-pharmacological treatments that can be given to patients with hyperuricemia is giving pineapple and soursop leaves pudding. The Aim Of The Research: The goal of this study is to see if giving pineapple and soursop leaves to hyperuricemic patients lowers their uric acid level. Research Method : this study uses a quasi – experimental design pretest and posttest with a control group. This study took place in Palembang’s Sosial Public Health Center from January to April 2022. In this study, the sample was chosen via random sampling selection, with a total of 39 respondents in the comparison and treatment group. The independent sample t-test and paired sample t-test were used to analyze the data. The Result : with average difference p - value of uric acid levels between the comparison group and the treatment group (p- value = 0.000). The independent sample t-test resulted in a p-value = 0.000. Conclusion : This means that giving pineapple and soursop leaves pudding has an effect on lowering levels of uric acid in hyperuricemic patients, with the average difference in uric acid level of the comparison group being lower than the treatment group.